2018
DOI: 10.1590/1980-549720180015.supl.2
|View full text |Cite
|
Sign up to set email alerts
|

Comparação do estado nutricional e da ingestão alimentar referida por idosos de diferentes coortes de nascimento (1936 a 1940 e 1946 a 1950): Estudo Saúde, Bem-Estar e Envelhecimento (SABE)

Abstract: RESUMO: Introdução: O processo de envelhecimento é caracterizado por várias alterações, incluindo do estado nutricional e da ingestão alimentar. Para compreender a tendência dessas alterações são necessários estudos com idosos de diferentes épocas de nascimento. Objetivo: Comparar o estado nutricional e a ingestão alimentar de idosos participantes do Estudo Saúde, Bem-Estar e Envelhecimento (SABE), realizado em São Paulo, em 2000 e 2010. Métodos: O estado nutricional foi identificado pelo índice de massa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
1
0
2
Order By: Relevance
“…The Brazilian National Dietary Survey, conducted in a sub-sample of the Household Budget Survey (NDS-HBS, in Portuguese Inquérito Nacional de Alimentação-Pesquisa de Orçamento Familiar-INA/POF) already showed that older persons had a higher prevalence of consumption of whole milk and lower consumption of eggs compared to adults 6 , but studies that compare the intake of speci c food groups between different age groups in older groups are rare. A study that compared the dietary intake of two cohorts of participants of SABE Study, in Sao Paulo, showed that those born between 1946 and 1950 (younger cohort) had signi cantly lower consumption of dairy products than the older cohort (born between 1936 and 1940); when the prevalence was evaluated separately by sex, this difference was signi cant only among men 14 . It is not possible to know the reasons involved in these differences, but it is possible to raise the hypothesis that the older participants in the present study have already received guidance from health professionals about the importance of dairy products in bone health, since they are the main sources of dietary calcium.…”
Section: Oliveira Et Al (2015)mentioning
confidence: 99%
“…The Brazilian National Dietary Survey, conducted in a sub-sample of the Household Budget Survey (NDS-HBS, in Portuguese Inquérito Nacional de Alimentação-Pesquisa de Orçamento Familiar-INA/POF) already showed that older persons had a higher prevalence of consumption of whole milk and lower consumption of eggs compared to adults 6 , but studies that compare the intake of speci c food groups between different age groups in older groups are rare. A study that compared the dietary intake of two cohorts of participants of SABE Study, in Sao Paulo, showed that those born between 1946 and 1950 (younger cohort) had signi cantly lower consumption of dairy products than the older cohort (born between 1936 and 1940); when the prevalence was evaluated separately by sex, this difference was signi cant only among men 14 . It is not possible to know the reasons involved in these differences, but it is possible to raise the hypothesis that the older participants in the present study have already received guidance from health professionals about the importance of dairy products in bone health, since they are the main sources of dietary calcium.…”
Section: Oliveira Et Al (2015)mentioning
confidence: 99%
“…A busca nas bases de dados Lilacs, Pubmed e literatura cinzenta encontrou oito, 738 e 70 artigos respectivamente. Foram incluídos na síntese de evidências sete trabalhos científicos [18][19][20][21][22][23][24] Adicionalmente, informações de materiais técnicos publicados pelo Ministério da Saúde 2-14 , e o relatório da POF 2017-2018, também apoiaram a elaboração do protocolo.…”
Section: Estruturação Do Protocolounclassified
“…Para avaliar a massa corporal total, foi utilizado o IMC, classificado segundo a Organização Pan Americana de Saúde (OPAS), 12 que leva em consideração a população brasileira, bem como as mudanças na composição corporal que ocorrem com o envelhecimento, quando comparados aos indivíduos adultos.…”
Section: Metodologiaunclassified